Quantitative analysis of the caloric restriction versus isocaloric diets models based on macronutrients composition: impacts on body weight regulation, anthropometric, and bioimpedance parameters in women with obesity - Pescari, Denisa; Mihuta, Monica Simina; Bena, Andreea; Stoian, Dana (Frontiers in Nutrition, 2024)
IntroductionObesity is a growing public health issue, especially among young adults, with long-term management strategies still under debate. This prospective study compares the effects of caloric restriction and isocaloric diets with different macronutrient distributions on body composition and anthropometric parameters in obese women during a 12-week weight loss program, aiming to identify the most effective dietary strategies for managing obesity-related health outcomes.MethodsA certified clinical nutritionist assigned specific diets over a 12-week period to 150 participants, distributed as follows: hypocaloric diets—low-energy diet (LED, 31 subjects) and very low-energy diet (VLED, 13 subjects); isocaloric diets with macronutrient distribution—low-carbohydrate diet (LCD, 48 subjects), ketogenic diet (KD, 23 subjects), and high-protein diet (HPD, 24 subjects); and isocaloric diet without macronutrient distribution—time-restricted eating (TRE, 11 subjects). Participants were dynamically monitored using anthropometric parameters: body mass index (BMI), waist circumference (WC), waist to hip ratio (WHR) and bioelectrical impedance analysis (BIA) using the TANITA Body Composition Analyzer BC-418 MA III (T5896, Tokyo, Japan) at three key intervals—baseline, 6 weeks, and 12 weeks. The following parameters were evaluated: body weight, basal metabolic rate (BMR), percentage of total body fat, trunk fat, muscle mass, fat-free mass, and hydration status.ResultsAll diets led to weight loss, but differences emerged over time. The TRE model resulted in significantly less weight loss compared to LED at the final follow-up (6.30 kg, p < 0.001), similar to the VLED (4.69 kg, p < 0.001). Isocaloric diets with varied macronutrient distributions showed significant weight loss compared to LED (p < 0.001). The KD reduced waist circumference at both 6 and 12 weeks (−4.08 cm, p < 0.001), while significant differences in waist-to-hip ratio reduction were observed across diet groups at 12 weeks (p = 0.01). Post-hoc analysis revealed significant fat mass differences at 12 weeks, with HPD outperforming IF (p = 0.01) and VLED (p = 0.003). LCD reduced trunk fat at 6 weeks (−2.36%, p = 0.001) and 12 weeks (−3.79%, p < 0.001). HPD increased muscle mass at 12 weeks (2.95%, p = 0.001), while VLED decreased it (−2.02%, p = 0.031). TRE showed a smaller BMR reduction at 12 weeks compared to LED.ConclusionThis study highlights the superior long-term benefits of isocaloric diets with macronutrients distribution over calorie-restrictive diets in optimizing weight, BMI, body composition, and central adiposity.